A development of Meeting Document Management System (MDMS) / Norhayati Saadah Che Abd Razak - Che Abd Razak, Norhayati Saadah (2006)
With today's emerging telecommunications technology, high-speed broadband networks, and the Internet, offices have become eclectically electromc. OflRce tasks that were performed manually for centuries have become electronic and some even virtual. The e-office uses telecommunications technology to provide electronic office administrative services to anyone, anywhere, anytime. The development of Meeting Document Management System (MDMS) help in centralized all the meeting documents. Currently meeting member does not have system that can help meeting member to shares and access meeting document. Meeting documents that hold by clerk are difficult to access because it is place in office. In order to get the document, they need to come at office clerk in working hour. To develop the prototype of MDMS, user requirements are gathered by interviews and questionnaires and also read secondary data. The module of Meeting Document Management System is design and developed using OpenACS framework.